1998
DOI: 10.1001/archinte.158.21.2373
|View full text |Cite
|
Sign up to set email alerts
|

Heartburn Requiring Frequent Antacid Use May Indicate Significant Illness

Abstract: Chronic heartburn can reflect a wide range of diagnostic findings, including important underlying pathological features, and may warrant a full medical examination to detect such abnormal conditions and to permit selection of appropriate therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
2

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(45 citation statements)
references
References 18 publications
(14 reference statements)
0
43
0
2
Order By: Relevance
“…The majority of patients with reflux symptoms have been reported not to have endoscopically proven erosive esophagitis, even though their symptoms are severe not only in western countries but also in Japan (4)(5)(6)(7)(8)(9)(10)(11)(12). We have recently clarified that 18% of Japanese subjects who attend hospital for annual health check-ups have reflux symptoms or endoscopically proven reflux esophagitis, and that over 80% of patients with reflux symptoms do not have erosive esophagitis (13).…”
Section: Gastroesophageal Reflux Disease (Gerd) Is Characterized By Tmentioning
confidence: 99%
“…The majority of patients with reflux symptoms have been reported not to have endoscopically proven erosive esophagitis, even though their symptoms are severe not only in western countries but also in Japan (4)(5)(6)(7)(8)(9)(10)(11)(12). We have recently clarified that 18% of Japanese subjects who attend hospital for annual health check-ups have reflux symptoms or endoscopically proven reflux esophagitis, and that over 80% of patients with reflux symptoms do not have erosive esophagitis (13).…”
Section: Gastroesophageal Reflux Disease (Gerd) Is Characterized By Tmentioning
confidence: 99%
“…Many people cope with severe disease without consulting a physician, as is demonstrated by the fact that up to half of individuals with GERD who self-medicate are found to have oesophagitis when they undergo endoscopy. 54,55 This finding suggests that it is not always appropriate for doctors to provide simple reassurance in the first instance.…”
mentioning
confidence: 99%
“…Results from a study that included 155 subjects with heartburn for an average of 11 years, with at least 3 months of frequent heartburn relieved by antacids, and with heartburn on at least 4 of 7 days during the week prior to study entry indicated that longterm antacid use may mask significant health issues. [25]. Endoscopy revealed hiatal hernia in 57% of subjects, erosive esophagitis in 47% of subjects, and nondyplastic Barrett's esophagus in 6% of subjects.…”
Section: Antacidsmentioning
confidence: 96%